Examining social problem solving programmes with mentally disordered and intellectually disabled offenders in secure hospital settings - Dhaliwal, Ranjit (2017)
This thesis examines the effectiveness of social problem solving programmes and the efficacy of an assessment tool designed for mentally disordered offenders (MDOs) and intellectually disabled (ID) offenders in secure hospital settings. Firstly, a systematic review concluded that all studies reported benefits of the social problem solving programmes with MDOs. Several studies also identified that shorter revised programmes had lower drop-out rates, and were more cost-effective. Methodological limitations were identified and suggested further research is needed.